Manipulation of innate immune signaling pathways by SARS-CoV-2 non-structural proteins - Lu, Yongxu; Michel, Hendrik A.; Wang, Pei-Hui; Smith, Geoffrey L. (Frontiers in Microbiology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of the current coronavirus disease 2019 (COVID-19) pandemic, induces an unbalanced immune response in the host. For instance, the production of type I interferon (IFN) and the response to it, which act as a front-line defense against virus invasion, are inhibited during SARS-CoV-2 infection. In addition, tumour necrosis factor alpha (TNF-α), a proinflammatory cytokine, is upregulated in COVID-19 patients with severe symptoms. Studies on the closely related betacoronavirus, SARS-CoV, showed that viral proteins such as Nsp1, Orf6 and nucleocapsid protein inhibit IFN-β production and responses at multiple steps. Given the conservation of these proteins between SARS-CoV and SARS-CoV-2, it is not surprising that SARS-CoV-2 deploys similar immune evasion strategies. Here, we carried out a screen to examine the role of individual SARS-CoV-2 proteins in regulating innate immune signalling, such as the activation of transcription factors IRF3 and NF-κB and the response to type I and type II IFN. In addition to established roles of SARS-CoV-2 proteins, we report that SARS-CoV-2 proteins Nsp6 and Orf8 inhibit the type I IFN response but at different stages. Orf6 blocks the translocation of STAT1 and STAT2 into the nucleus, whereas ORF8 inhibits the pathway in the nucleus after STAT1/2 translocation. SARS-CoV-2 Orf6 also suppresses IRF3 activation and TNF-α-induced NF-κB activation.